Success of medicaments and techniques for pulpotomy of primary teeth: An overview of systematic reviews. Issue 6 (26th April 2022) - Tewari, Nitesh; Goel, Shubhi; Mathur, Vijay Prakash; O'Connell, Anne C.; Johnson, Riya Marie; Rahul, Morankar; Sultan, Farheen; Goswami, Mridula; Srivastav, Sukeshana; Ritwik, Priyanshi
Abstract: Background: Pulpotomy is an effective, vital pulp therapy procedure for caries‐affected or traumatized primary teeth. Though its efficacy is widely accepted, the superiority of medicaments and techniques remains debatable. Aim: The aims of this review were to compare the success rates of various pulpotomy medicaments or techniques, assess the methodological quality of reviews, and grade the level of evidence for each comparison. Design: This review followed the principles of evidence‐based medicine and recommendations for the overview of systematic reviews. An a priori protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO; CRD42021244489). A comprehensive literature search was performed by two reviewers, and studies were selected from various databases according to predefined criteria. Two reviewers independently used a self‐designed pilot‐tested form to extract data from the selected studies. A quality analysis was performed using A MeaSurement Tool to Assess systematic Reviews‐2 (AMSTAR‐2) and the ROBIS tool. Reporting characteristics and overlap of the primary studies were also assessed. We used modified Köhler's criteria for evaluating the quality of evidence for outcomes of included systematic reviews and meta‐analyses. Results: The scrutiny of 62 full‐text articles resulted in the inclusion of eight systematic reviews. The quality of four of the reviews was found to be critically low, and the overlap of primary studies in the meta‐analyses was found to be high. Pulpotomy medicaments/techniques, except calcium hydroxide, had success rates of more than 80% for all domains and time periods. Most of the comparisons revealed no differences in the clinical, radiographic, or overall success rates. Mineral trioxide aggregate, however, was found to have better radiographic and overall success rates than calcium hydroxide at periods greater than 12 and 18 months. It also had a greater radiographic success rate than full‐strength/1:5 diluted and full‐strength formocresol at 24 months. Formocresol was found to have better overall success rates than calcium hydroxide at all time periods and better radiographic success rates at 12 months. Only 12 of the 63 comparisons had suggestive or weak evidence, whereas all others had either negligible evidence or insufficient data. Conclusions: The pulpotomy medicaments/techniques, except calcium hydroxide, showed success rates of more than 80%, whereas most comparisons revealed no differences. Mineral trioxide aggregate, however, was found to be better than calcium hydroxide and formocresol in several respects. This study highlights the lack of evidence regarding the choice of pulpotomy agents for the treatment of caries‐affected primary teeth and elucidates the domains that require primary studies in the future.